Os histiócitos e as histiocitoses não Langerhans em dermatologia Histiocytes and non-Langerhans cell histiocytoses in dermatology - Flávio Barbosa Luz; Antônio Pedro Gaspar; Neide Kalil-Gaspar; Márcia Ramos- (Sociedade Brasileira de Dermatologia, 2003)
Atualmente, os histiócitos não são mais compreendidos como células únicas, mas como um grupo heterogêneo de células com o mesmo aspecto histológico, mas com características e funções distintas entre si. Várias doenças proliferativas de histiócitos, conhecidas como histiocitoses, são descritas. Tais doenças são raras, e seu estudo costuma ser difícil. Este artigo objetiva simplificar o entendimento desse grupo de doenças, adequando-o a esse novo paradigma da heterogeneidade dos histiócitos. Histiocytes are no longer recognized as singular cells. The term 'histiocyte' now refers to a heterogeneous group of cells with unique histologic morphology, but with singular functions and characteristics. Histiocytoses are a group of different diseases caused by proliferative histiocytes. Such diseases are rare and their study usually tends to be difficult. The objective of this paper is to simplify the study of these diseases under the novel paradigm of histiocyte heterogeneity.